Helping Students Making Better Future: Factors Affecting College of Business Selection - Alshammari, Hammad; Tripathi, Abhishek (Advances in Social Sciences Research Journal, 2017)
The purpose of the study is to identify the factors that motivates students to join a degree college in the university. The study was conducted at College of Business, University of Hail, Saudi Arabia. Various tools and techniques applies to identify the motivational factors. Four important factors such as academic influence, family and peers influence, personal factors and job opportunities were identified through factor analysis which plays a pivotal role for the students to join the college.ANOVA was also used to know the significant impact of these four factors across gender. It has been found that personal factors, family and peers influence and job opportunities has a significant impact while selecting a college. However, Academic influence was not significance to students when selecting colleges and based on this results recommendations were given.